2007
DOI: 10.1590/s0004-27302007000300012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da deficiência, insuficiência de vitamina D e hiperparatiroidismo secundário em idosos institucionalizados e moradores na comunidade da cidade de São Paulo, Brasil

Abstract: A ocorrência de fraturas osteoporóticas em idosos está relacionada às concentrações reduzidas de vitamina D e conseqüente hiperparatiroidismo secundário, sendo os institucionalizados de maior risco. No Brasil, por seu alto grau de insolação, infere-se que a quantidade de vitamina D da população seja adequada. Neste estudo, objetivamos avaliar as concentrações plasmáticas de 25-hidroxivitamina D (25OHD), paratormônio (PTH) e cálcio ionizado (Cai), assim como analisar a prevalência de hipovitaminose D e de hiper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
21

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 30 publications
1
37
0
21
Order By: Relevance
“…The prevalence of vitamin D inadequacy (defined as < 30 ng/mL) was over 50% in all five world regions, and was highest in the Middle East (81%) and Asia (63%) (17). In Brazil, a cross-sectional study evaluated serum levels of 25-hydroxyvitamin D [25(OH)D] in the elderly living in the city of São Paulo, the authors observed that 71.2% of the inpatient group and 43.8% of the outpatient group had 25OHD levels below the minimum recommended (50 nmol/L) (18). Vitamin D insufficiency was also observed in 24% of women with osteoporosis (19).…”
Section: Vitamin Dmentioning
confidence: 99%
“…The prevalence of vitamin D inadequacy (defined as < 30 ng/mL) was over 50% in all five world regions, and was highest in the Middle East (81%) and Asia (63%) (17). In Brazil, a cross-sectional study evaluated serum levels of 25-hydroxyvitamin D [25(OH)D] in the elderly living in the city of São Paulo, the authors observed that 71.2% of the inpatient group and 43.8% of the outpatient group had 25OHD levels below the minimum recommended (50 nmol/L) (18). Vitamin D insufficiency was also observed in 24% of women with osteoporosis (19).…”
Section: Vitamin Dmentioning
confidence: 99%
“…In Brazil, studies carried out in the city of São Paulo show the high prevalence of hypovitaminosis D, both in healthy adolescents (9) and in elderly populations, either institutionalized or not (4). In Recife, a city of tropical humid climate, there was a high prevalence of vitamin D deficiency associated with low bone density in a study carried out with menopausal women (10).…”
mentioning
confidence: 97%
“…From the skin, vitamin D 3 gets into the circulation and undergoes a first hydroxylation in the liver, yielding 25(OH)D (calcidiol), the most abundant and stable vitamin D metabolite, which is considered the best indicator of the status of this vitamin in the body (2). After that, circulating calcidiol reaches the kidneys, where it undergoes new hydroxylation and is converted to 1,25(OH) 2 D (calcitriol), an active form of the hormone that acts on several types of cells by means of its nuclear receptor (3), stimulating, for example, the intestinal absorption of calcium and bone mineralization, and regulating the synthesis and secretion of parathormone (PTH) (4).…”
mentioning
confidence: 99%
“…In this assessment, 71.2% of the institutionalized group and 43.8% of the outpatients have shown values of 25 OHD lower than the minimum level recommended (50 nmol/L). 20 In our study of vitamin D in Brazilian men, outpatients aged 50 years or older in Rio de Janeiro (n = 152), we observed high prevalence of hypovitaminosis D (49.4%) and deficiency of vitamin D (31. 9%).…”
Section: Discussionmentioning
confidence: 70%